Ga@C-dots as an antibacterial agent for the eradication of Pseudomonas aeruginosa - Kumar VB (Dove Medical Press, 2017)
Vijay Bhooshan Kumar,1 Michal Natan,2 Gila Jacobi,2 Ze’ev Porat,3,4 Ehud Banin,2 Aharon Gedanken1,5 1Department of Chemistry, 2Mina and Everard Goodman Faculty of Life Sciences, Bar Ilan Institute for Nanotechnology and Advanced Materials Bar-Ilan University, Ramat Gan, 3Division of Chemistry, Nuclear Research Center-Negev, 4Institutes of Applied Research, Ben-Gurion University of the Negev, Be’er-Sheva, Israel; 5National Cheng Kung University, Department of Materials Science and Engineering, Tainan, Taiwan Abstract: The opportunistic pathogen Pseudomonas aeruginosa causes infections that are difficult to treat by antibiotic therapy. This research article reports on the synthesis of gallium (Ga) doped in carbon (C)-dots (Ga@C-dots) and their antimicrobial activity against free-living P. aeruginosa bacteria. The synthesis of Ga@C-dots was carried out by sonicating molten Ga (for 2.5 h) in polyethylene glycol-400, which acts as both a medium and carbon source. The resultant Ga@C-dots, having an average diameter of 9±2 nm, showed remarkably enhanced antibacterial activity compared with undoped C-dots. This was reflected by the much lower concentration of Ga doped within Ga@C-dots which was required for full inhibition of the bacterial growth. These results highlight the possibility of using Ga@C-dots as potential antimicrobial agents. Keywords: C-dots, Ga@C-dots, sonochemistry, gallium, antibacterial, Pseudomonas aeruginosa